2000
DOI: 10.26719/2000.6.2-3.265
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of urinary tract infection during pregnancy

Abstract: Incidence of urinary tract infection [UTI] during pregnancy among Pakistani women was examined. Midstream urine was collected from 250 pregnant and 100 control women and streaked on blood agar and incubated. Growth was considered significant if > / = 10[5]/mL bacteria were present. Among the pregnant women, 28.5% had UTI; 30.0% of controls had UTI. Among the pregnant and control women, 24.4% and 20.0% respectively had UTI symptoms, such as incontinence, nocturia and urgency. Symptoms did not correlate with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 0 publications
2
6
0
1
Order By: Relevance
“…The high percent of infection may be back to the majority of females in current work belonged to socioeconomic with lower and/or middle levels; this theory is supported by various studies that referred that the UTI has happened at a higher rate among pregnant females living in status with poor socioeconomic [13][14]. The isolated bacteria from the urine sample in the present work was E. coli and this agreed with the findings of previous studies [15][16][17][18]. The flora located in faeces serves as the source of E. coli that colonizes the introitus of the vagina and urethra to bladder infection [19].…”
Section: Resultssupporting
confidence: 91%
“…The high percent of infection may be back to the majority of females in current work belonged to socioeconomic with lower and/or middle levels; this theory is supported by various studies that referred that the UTI has happened at a higher rate among pregnant females living in status with poor socioeconomic [13][14]. The isolated bacteria from the urine sample in the present work was E. coli and this agreed with the findings of previous studies [15][16][17][18]. The flora located in faeces serves as the source of E. coli that colonizes the introitus of the vagina and urethra to bladder infection [19].…”
Section: Resultssupporting
confidence: 91%
“…Pastore et al identified two strongest predictors of bacteriuria at prenatal care to be antepartum UTI prior to prenatal care and a prepregnancy history of UTI 17 . Same was observed by Sheikh et al 18 . This study also showed a high figure of UTI in women with a abnormal voiding pattern and positive past history of UTI.…”
Section: Agesupporting
confidence: 81%
“…Other studies have also indicated that a lower number of prenatal visits increases the risk of anemia (15). In studies conducted in Egypt, Pakistan, Libya, and Ethiopia, the prevalence of UTI was 32%, 23.9%, 30%, and 15.3%, respectively (3,(16)(17)(18). The combined overall prevalence of UTI among pregnant women in Khash was estimated at 49%.…”
Section: Discussionmentioning
confidence: 99%